Dampak Role Ambiguity Dan Role Conflict Terhadap Turnover Intention Melalui Stres Kerja Pada Perawat RS Roemani Muhammadiyah - Regita Layla; Annisa Fajri (Universitas Muhammadiyah Pontianak, 2026)
This study aims to analyze the factors of Role Ambiguity and Role Conflict on Turnover Intention through Work Stress among nurses at Roemani Muhammadiyah Hospital in Semarang. The method used is quantitative with 135 respondents, and SmartPLS 4.0 is used as the data analysis tool. The results show that Role Ambiguity and Role Conflict have a significant effect on Turnover Intention. This explains that when nurses experience Role Ambiguity and Role Conflict, their personal resources will be depleted, which will ultimately increase work stress.